Jumping spider (Araneae: Salticidae) diversity in the understory of the Argentinian Atlantic Forest (2017)
The Atlantic Forest is one of the key biodiversity hotspots in the world. Its understory can be dominated by species such as the native bamboo Chusquea ramosissima (tacuarembó), which can be an aggressive gap colonizer and change biotic and abiotic conditions compared to mature forest. A strong association has been observed between Salticidae spiders and microhabitat type, frequently linked to host plant structure. Since little is known about the diversity of spiders in tree-fall gaps of the Atlantic Forest, the differences in the Salticidae assemblages between three habitats –the understory of typical forest, Bamboo gaps (dominated by tacuarembó) and restoration areas (tacuarembó removal)– were explored in the southern tip of the Atlantic Forest, Upper Parana Atlantic Forest ecoregion in Misiones province, Argentina. A total of 515 jumping spiders (32 species; 106 adults) were collected. Differences in species composition were detected between habitats, where Forest understory and Bamboo gaps differ in almost 50% of the species. Bamboo gaps had the highest number of exclusive species, but the three habitats did not differ in their average taxonomic diversity indices. In addition, richness was higher in Bamboo gaps compared to Forest understory, which may reflect higher niche diversity in the former habitat.